Next Generation Access in a Rural Community Context: An Innovation Analysis - ELIZABETH COPE (2022)
This thesis explores how to resolve the digital divide in Wales. This is important because access to advanced broadband is considered an essential requirement, particularly post-COVID19. UK Government is advocating next generation access (NGA) to capitalise on Industry 4.0. However, the financial costs and complexities of connecting the final few rural areas is a persisting problem area. Hence, this thesis explores new innovative approaches to provide NGA (product) to a final few (market). Studies revealed superfast broadband in remote rural communities has four-fold human, social, environmental and financial capital benefits. Analysis resulted in a new conceptual framework which combines neo-endogenous theories alongside a four-fold capital model to characterise the complex ecosystem. Previous literature focused on either supply or demand, but few studies had investigated both together at the local level. Human & social capital were identified as critical success factors in community-led initiatives, thus providing a theoretical underpinning for this thesis. This study employed a novel mutual business approach utilising the Hybrid Value System (HVS) as an ecosystem connecting the core assets of several stakeholders. Furthermore, the World Bank Social Capital Assessment Tool was modified to investigate social capital fertility to enhance investment. Henceforth, a qualitative multi-method and in-depth intrinsic case study was used to explore the ecosystem. The contribution to knowledge is how to engage multi-stakeholder and multi-capital analysis to resolve the problem area. The results identified human capital productivity, social capital collective action, and shared financial capital are required at the local level to reach the final few. The mutual business paradigm challenges all stakeholders to value non-financial capital alongside financial capital for problem area resolution. This thesis concludes that HVS methodology coupled with complex ecosystem-network visualisation techniques, provide academics, management and government policy makers with practical tools to value four-fold capital resources and bridge the digital divide.